ANALISIS PERTUMBUHAN LABA PERUSAHAAN PROPERTY AND REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Kartika, Felia Lita; Nur, Dhani Ichsanuddin (Jurnal Manajemen Akuntansi (JUMSI), 2021)
Profit growth is a ratio that shows the percentage of profit earned by a company. This study aims to examine and analyze the effect of working capital on total assets, debt to asset ratio, and total asset turnover on profit growth in property and real estate companies listed on the Indonesia Stock Exchange in 2016-2019. Determination of the sample in this study is a purposive sampling technique. The sample used in this study were 29 property and real estate companies on the Indonesia Stock Exchange in 2016-2019. The analytical method used in this research is multiple linear regression analysis. Hypothesis testing is done using the F test (simultaneous test) and t test (partial test). The results of this study indicate that working capital to total assets and debt to asset ratio does not contribute to profit growth in property and real estate companies on the Indonesia Stock Exchange. Meanwhile, total asset turnover contributed to profit growth in property and real estate companies on the Indonesia Stock Exchange.